Management of Corporate Zakat on Sharia Banking - Shopia Marwah Rangkuti; Mustapa Khamal Rokan (Journal of Indonesian Management, 2022)
This study focuses on the management of corporate zakat on Islamic banking. The purpose of the study was to determine the management of the company's zakat on Islamic banking. The method used in this study is a qualitative method, namely a research method based on philosophy used to examine the condition of natural objects, where the researcher is the key instrument, collecting data using literature studies such as taking from clear and accurate reading sources. The result of this research is to understand the company's zakat management towards sharia banking.